ANALISIS RESPON PETANI TERHADAP PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KECAMATAN LAWANG, KABUPATEN MALANG - Maylatul Chasanah; Dwi Purnomo; Ugik Romadi (Jurnal Sosial Ekonomi Pertanian, 2020)
This study is a survey that aims to: 1) Describe the implementation of the KRPL program in Lawang Subdistrict, 2) Analyze the responses of farmers to the KRPL program in Lawang District, and 3) Analyze the influence of age, education, number of family members, income, yard area, perception and motivation towards farmer response to the KRPL program. This research was conducted in Ketindan and Kalirejo Village, Lawang District, Malang Regency. Determination of the research location was carried out purposively with the criteria that Lawang Subdistrict was the KRPL program recipient area. The object of study was the member of two female farmers Lawang District which received the KRPL program consist of 21 farmers from Teratai female farmers association and 25 farmers from Wanodyo female farmer association. The research using quantitative paradigm and conducted with survey techniques. Analysis of the data used included tests of validity, reliability, t test, normality test, multicollinearits, heteroscedasticity and multiple linear regression analysis. The results showed that: 1) The KRPL program was developed in Lawang Subdistrict as an effort to optimize the use of yard and food diversification in overcoming food insecurity in Malang Regency, 2) The level of farmers' response to the development of the KRPL program was 87% while the remaining 13% were still unsure , and 3) Factors that significantly influence the response of farmers in implementing the KRPL program in Lawang District, Malang Regency are the perceptions and motivations of farmers.